Investigation of the Prevalence of HPV DNA Types 16, 18, 31 and 33 in Malignant Lesions of the Upper Respiratory Tract - Korkmaz, Ebru; Bulut, Yasemin; Seyrek, Adnan; Ozercan, I. Hanifi; Toramana, Zulal Asci (Ortadogu Ad Pres & Publ Co, 2010)
Objective: The aim of the present study was to determine the frequency and types of human papillomavirus (HPV) in malignant lesions of the upper respiratory tract. Material and Methods: As case group, the paraffinized tissue samples from 75 patients diagnosed as epidermoid carcinoma of the upper respiratory tract were analyzed with the polymerase chain reaction (PCR) method for the detection of the presence of human papillomavirus. Samples from 25 patients with benign lesion of the upper respiratory tract were used as the control group. HPV type 16, 18, 31 and 33 were determined by using type-specific primers. Results: Twenty-five (33%) of 75 tissue samples from patients with carcinoma of the upper respiratory tract were found positive for HPV DNA. Among these HPV positive samples, 11(44%) were HPV DNA type 16 positive, and eight samples (32%) were HPV DNA type 18 positive. In one patient, HPV DNA type 16 and HPV DNA type 18 positivity were found together. Four (16%) of 25 samples with benign lesions were found positive for HPV DNA. Among these samples, one (25%) was HPV DNA type 16 and one (25%) was HPV DNA type 18 positive. Conclusion: The results of this study suggest that, althought HPV DNA type 16 and HPV DNA type 18 are often found in the malignant lesions of the upper respiratory tract, there was not statistically significant difference between the presence of HPV DNA and tumor (p>0.05). However, more comprehensive studies are required to elucidate the epidemiology of HPV infections in Turkey.
Üst solunum yolları malign lezyonlarında HPV tip 16, 18, 31 ve 33 DNA prevalansının araştirilmasi
Keywords: Human papillomavirus; polymerase chain reaction; epidermoid carcinoma